(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Introduction: Accurate clinical coding is essential for effective medical billing and the overall efficiency of healthcare systems. Precise coding impacts not only the financial aspects of healthcare but also the quality of patient care and administrative decision-making. Despite its importance, hospitals often face challenges such as poor documentation, inadequate coding tools, and organizational barriers that hinder the effectiveness of coding practices. These issues can lead to inaccuracies in billing and inefficiencies in healthcare delivery, which necessitates a comprehensive examination of coding practices and their impact. Objective: This study aims to evaluate the impact of accurate coding in health records on billing accuracy in selected hospitals within Ibadan North Local Government, Oyo State. Method: Data were collected through a structured questionnaire administered to health information management professionals. The data were analyzed using descriptive statistics, including mean scores and standard deviations, calculated with SPSS Version 20. Results: Analysis of the responses revealed that 57.3% of participants strongly agreed they have knowledge about clinical coding and billing, with a mean score of 1.5043 (SD = 0.6775). Furthermore, 53% strongly agreed they practice clinical coding, and 44.4% strongly agreed they practice medical billing, although there was variability in responses regarding specialized training. Factors affecting accuracy included poor documentation (mean = 1.8632, SD = 0.9640) and inadequate coding tools (mean = 1.6667, SD = 0.9191). Accurate coding was seen as significantly improving healthcare quality (mean = 1.2564, SD = 0.43853) and administrative decision-making (mean = 1.2991, SD = 0.45985). Solutions proposed included better training and improved technology. Conclusion: The study underscores the critical role of accurate coding in enhancing billing accuracy and overall healthcare management. Addressing challenges such as documentation quality and resource adequacy through targeted improvements can significantly advance billing practices and healthcare delivery.